Revitalizing Toddler Posyandu with Health Cadre Training - Zulfa Rufaida; Sri Wardini Puji Lestari; Yudha Laga Hadi Kusuma (JURNAL PENGABDIAN MASYARAKAT KESEHATAN (ABDIMAKES), 2021)
According to the current data there are thousands of Posyandu that are lost, both in terms of activities, existence, and physically. While the number of active cadres is also decreasing, it is feared that it can significantly reduce the reach of health services. Health cadres around the community must have a high level of knowledge about health that occurs in the community. Health cadres are the right target in the implementation of health programs because they are considered as the first place of reference for health services, (Wang et al, 2012). The purpose of this community service is to revitalize toddler posyandu through health cadre training. The training method used is the method of lecture, discussion, role play and mentoring, the target is health cadres in Sumbertebu Village, Bangsal District, Mojokerto Regency, carrying out activities from September to November 2018. Data analysis uses frequency distribution. The results obtained were as many as 26 trainees with the results of the means pre test 49.62 and post test 92.69. The result is a significant increase in knowledge 0,000 with a value of t = -17.93, and 95% CI between -48.03 - -38.13, meaning that the effect is strong because it does not pass the number 1; giving treatment can increase 3 - 4x knowledge compared to not given. Whereas for the assistance of posyandu activities for toddlers, the presence of health cadres and community leaders is on average 7 people. Participants in the training of health cadres were enthusiastic about the material presented, the participants were active in the discussion activities with evidence of feedback. The lack of knowledge of health cadres resulted in a lack of understanding of health cadres on the role and importance of posyandu activities, which led to low visits to posyandu. Support from families, community leaders and health workers is needed to always motivate health cadres in carrying out their duties at the Posyandu every month. Keywords: Health Cadres, Toddler Posyandu